Acute changes in neuromuscular excitability after exhaustive whole body vibration exercise as compared to exhaustion by squatting exercise - Rittweger, J.; Mutschelknauss, M.; Felsenberg, D. (Clinical Physiology and Functional Imaging, 2003)
The effects of hard squatting exercise with (VbX+) and without (VbX)) vibration on neuromuscular function were tested in 19 healthy young volunteers. Before and after the exercise, three different tests were performed: maximum serial jumping for 30 s, electromyography during isometric knee extension at 70% of the maximum voluntary torque, and the quantitative analysis of the patellar tendon reflex. Between VbX+ and VbX- values, there was no difference found under baseline conditions. Time to exhaustion was significantly shorter in VbX+ than in VbX- (349 ± 338 s versus 515 ± 338 s), but blood lactate (5.49 ± 2.73 mmol l)1 versus 5.00 ± 2.26 mmol/l) and subjectively perceived exertion (rate of perceived exertion values 18.1 ± 1.2 versus 18.6 ± 1.6) at the termination of exercise indicate comparable levels of fatigue. After the exercise, comparable effects were observed on jump height, ground contact time, and isometric torque. The vastus lateralis mean frequency during isometric torque, however, was higher after VbX+ than after VbX-. Likewise, the tendon reflex amplitude was significantly greater after VbX+ than after VbX- (4.34 ± 3.63 Nm versus 1.68 ± 1.32 Nm). It is followed that in exercise unto comparable degrees of exhaustion and muscular fatigue, superimposed 26 Hz vibration appears to elicit an alteration in neuromuscular recruitment patterns, which apparently enhance neuromuscular excitability. Possibly, this effect may be exploited for the design of future training regimes.